Dry and Rainy Seasons Significantly Alter the Gut Microbiome Composition and Reveal a Key Enterococcus sp. (Lactobacillales: Enterococcaceae) Core Component in Spodoptera frugiperda (Lepidoptera: Noctuidae) Corn Strain From Northwestern Colombia. Issue 6 (4th November 2021) - Higuita Palacio, Marlon Felipe; Montoya, Olga I; Saldamando, Clara I; García-Bonilla, Erika; Junca, Howard; Cadavid-Restrepo, Gloria E; Moreno-Herrera, Claudia Ximena
Abstract: Spodoptera frugiperda is a polyphagous pest of several crops of economic importance. Nowadays, the insect is broadly distributed in America and, recently, in Africa, Asia, and Australia. The species has diverged into corn and rice strains. The role of the gut microbiota in insect physiology is relevant due to its participation in crucial functions. However, knowledge of seasonal variations that alter the gut microbiome in pests is limited. Gut microbiome composition between the dry and rainy seasons was analyzed with cultured and uncultured approaches in S. frugiperda corn strain larvae collected at Northwest Colombia, as seasonal microbiome changes might fluctuate due to environmental changes. On the basis of culture-dependent methods, results show well-defined microbiota with bacterial isolates belonging to Enterococcus, Klebsiella (Enterobacteriales: Enterobacteriaceae), Enterobacter (Enterobacterales: Enterobacteriaceae), and Bacillus (Bacillales: Bacillaceae) genera. The community composition displayed a low bacterial diversity across all samples. The core community detected with uncultured methods was composed of Enterococcus, Erysipelatoclostridium (Erysipelotrichales: Erysipelotrichaceae), Rasltonia (Burkholderiales: Burkholderiaceae), and Rhizobium (Hyphomicrobiales: Rhizobiaceae) genera, and Enterobacteriaceae family members. Significant differences in microbiome diversity were observed between the two seasons. The relative abundance of Erysipelatoclostridium was high in the dry season, while in the phylotype ZOR0006 (Erysipelotrichales: Erysipelotrichaceae) and Tyzzerella (Lachnospirales: Lachnospiraceae) genus, the relative abundance was high in the rainy season. The overall low gut bacterial diversity observed in the S. frugiperda corn strain suggests a strong presence of antagonist activity as a selection factor possibly arising from the host, the dominant bacterial types, or the material ingested. Targeting the stability and predominance of this core microbiome could be an additional alternative to pest control strategies, particularly in this moth.